2021
DOI: 10.1080/13636820.2021.1931945
|View full text |Cite
|
Sign up to set email alerts
|

Tackling regional skill shortages: from single employer strategies to local partnerships

Abstract: This research examines regional skill problems and the strategies implemented to reduce skill shortages by a set of employers (n=16). The data collected in 2019 in a northern region in Portugal indicate considerable and persistent shortages of engineering and IT graduates and non-graduates for operational jobs. The employers implement anticipative strategies interacting with the education system, and the city council has developed a multi-stakeholder partnership.However, the most widespread strategy is remedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Such an approach could help to build a richer picture and a more nuanced understanding of how to enhance the employability of domestic and international students. It could also help tackle national and regional skills shortages (Suleman et al, 2023) by developing a talent pipeline from higher education institutions into the labour market (Baruch et al, 2023).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Such an approach could help to build a richer picture and a more nuanced understanding of how to enhance the employability of domestic and international students. It could also help tackle national and regional skills shortages (Suleman et al, 2023) by developing a talent pipeline from higher education institutions into the labour market (Baruch et al, 2023).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Employers frequently complain about graduates' skills, and the education system is often thought to be to blame (Cappelli 2015;Suleman and Laranjeiro 2018;Suleman, Videira and Araújo 2021). These issues are captured through the concept of employability which focuses on the relationship between HE and the workplace (Römgens, Scoupe & Beausaert 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that an essential part of the employability agenda involves the employers and HE institutions working together in several key areas. Available research highlights a range of skill problems identified by employers, namely skill gaps that affect the individual's performance within the firm; and skill shortages, which lead to hard-to-fill vacancies; and under or oversupply, i.e., skill mismatch (Cappelli 2015;Suleman, Videira & Araújo 2021). It seems that employers blame HE institutions for their skill problems and expect them to produce graduates with the skills they require.…”
Section: Introductionmentioning
confidence: 99%